The importance of recruitment and retention in Heliophysics: it’s not just a pipeline problem - Halford, Alexa J.; Bard, Christopher M.; Burrell, Angeline G.; McGranaghan, Ryan M.; Wilson III, Lynn B.; Jones, McArthur; Dong, Chuanfei; Wang, Liang; Pulkkinen, Tuija I.; Turner, Niescja; Liemohn, Michael W.; Klenzing, Jeff (Frontiers in Astronomy and Space Sciences, 2023)
A major obstacle in cultivating a robust Heliophysics (and broader scientific) community is the lack of diversity throughout science, technology, engineering, and mathematics (STEM) fields. For many years, this has been understood as a “leaky pipeline” analogy, in which predominately minority students initially interested in STEM gradually fall (or are pushed) out of the field on their way to a scientific research position. However, this ignores critical structural and policy issues which drive even later career Ph.D.s out of a career in Heliophysics. We identify here several systemic problems that inhibit many from participating fully in the Heliophysics community, including soft money pressure, lack of accessibility and equity, power imbalances, lack of accountability, friction in collaboration, and difficulties in forming mentorship bonds. We present several recommendations to empower research-supporting organizations to help create a culture of inclusion, openness, and innovative science.